Comparison of Anesthesia Methods in Treatment of Staghorn Kidney Stones with Percutaneous Nephrolithotomy - Buldu, Ibrahim; Tepeler, Abdulkadir; Kaynar, Mehmet; Karatag, Tuna; Tosun, Muhammed; Umutogluv, Tarik; Tanriover, Hakan; Istanbulluoglu, Okan (Urology Journal, 2016)
Purpose: To compare the efficacy and safety of percutaneous nephrolithotomy (PNL) in the treatment of staghorn calculi (SC) under spinal anesthesia (SA) versus general anesthesia (GA). Materials and Methods: Patients with SC who treated with PNL from 2011 to 2014 were retrospectively reviewed. In total, 100 patients were divided into 2 groups according to anesthesia type: SA (group 1, n = 47) and GA (group 2, n = 53). Demographics, perioperative parameters, and postoperative analgesic requirements were compared between the two groups. Results: There was no significant difference in terms of age, sex, American Society of Anesthesiologists score, body mass index, or stone size between the two groups (P = .40, .30, .18, .20, and .50, respectively). The mean procedure times were 84.7 and 87.5 min in the SA and GA groups, respectively (P = .68). The complication rates were similar in the SA and GA groups (19.1% vs. 13.2%, respectively; P = .421). The stone-free rates were also similar in the SA and GA groups (61.7% vs. 52.8%, respectively; P = .374). No statistically significant difference was found in analgesic requirements. Conclusion: SA is a safe method without the risks of GA and may be used for conditions in which GA is contraindicated or in patients with concerns about GA. Our outcomes indicated that SC can be treated safely and effectively under SA.